2017
DOI: 10.4236/health.2017.92025
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among Physicians and Methodological Similarities of MEDLINE/PubMED and BVS/BIREME Open Access Bibliographic Databases: A Systematic Review with Metanalysis

Abstract: Background: Suicide among physicians is a serious public health issue, with an extremely complex and multifactorial behavior. Aim: The aim of this study was to use the theme "Suicide among Physicians" to exemplify the analysis of methodological similarities between the scientific content available at MEDLINE and BVS databases, as scientific research tools. Methods: This is a systematic review with metanalysis. The following combinations of keywords were used for data search in the referred databases: "suicide"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Around one million deaths by suicide behavior are registered every year ( 1 ), which is one person every 40 s and 1.4% of all deaths worldwide, being the 18th leading cause of death in 2016. Thus, suicide behavior is a global phenomenon and occurs throughout the life span ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around one million deaths by suicide behavior are registered every year ( 1 ), which is one person every 40 s and 1.4% of all deaths worldwide, being the 18th leading cause of death in 2016. Thus, suicide behavior is a global phenomenon and occurs throughout the life span ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Around 1 million deaths by suicide are registered every year-17% of them are related to Indians and 14% happen in developed countries [1]. International data indicate that suicides are more frequent among physicians than among members of distinct areas [2].…”
mentioning
confidence: 99%
“…A study found three work-related characteristics that are also related to the fact of not seeking help for depression: being currently involved in a medical research, being a surgeon and working at night shifts [1]. The academic clinical environment can be rigorous while dealing with medical research, clinical work and teaching.…”
mentioning
confidence: 99%
See 1 more Smart Citation